2014
DOI: 10.1007/s11657-014-0192-1
|View full text |Cite
|
Sign up to set email alerts
|

Women’s perspectives and experiences on screening for osteoporosis (Risk-stratified Osteoporosis Strategy Evaluation, ROSE)

Abstract: In general, the women accepted the screening program. No major ethical reservations or adverse psychological consequences were detected. Only a minority of women declined screening participation due to a low perceived risk of osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(60 citation statements)
references
References 30 publications
6
54
0
Order By: Relevance
“…Descriptions suggested a lack of trust in one's body and a view of the osteoporotic body as nonnormative and relied on metaphors of destruction and frailty [21]. A focus on physical characteristics or appearance for assessing osteoporosis risk has been identified in other samples of older Danish women [22]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Descriptions suggested a lack of trust in one's body and a view of the osteoporotic body as nonnormative and relied on metaphors of destruction and frailty [21]. A focus on physical characteristics or appearance for assessing osteoporosis risk has been identified in other samples of older Danish women [22]. …”
Section: Resultsmentioning
confidence: 99%
“…Patients do not connect underlying bone health to the resultant fractures, which are perceived as freak, traumatic accidents [26, 29]. A conceptualization of fractures as freak events has been reported by other authors (e.g., [22, 30, 31]). This dissociation had important impacts on medication adherence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A Canadian study of osteoporosis patients' perception of their care pathway following a lowenergy fracture [11] concluded that, when improving the uptake of osteoporosis testing and care, patients' awareness of their needs should be matched with the delivery of immediate information by a health care professional. While a Danish qualitative study of elderly women's experiences of screening for osteoporosis found no major adverse psychological consequences of screening for osteoporosis, the importance of patients' knowledge of the disease was highlighted [12]. However, based on a study of Danish elderly women's ideas of osteoporosis, Reventlow suggested, that the result of osteoporosis investigation and its cultural interpretation could trigger a reconstruction of the body-self as weak and having reduced capacity [13].…”
Section: Introductionmentioning
confidence: 99%